2016
DOI: 10.15171/ijep.2016.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antibacterial Activities of Citrus limon, Citrus reticulata, and Citrus grandis Against Pathogenic Bacteria

Abstract: Background Nowadays, bacteria are considered as the main cause of morbidity and mortality in many developing countries, especially amongst children. Among the bacterial pathogens, Escherichia coli, Salmonella spp, and Staphylococcus aureus are most prevalent. 1 In the recent decades despite developments of different types of antibiotics by pharmacological industries, resistance to antibiotics has been increased significantly in many bacterial pathogens. In general, bacteria have several genetic mechanisms to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 4 publications
2
22
0
1
Order By: Relevance
“…Indeed, the lemon leaf essential oil was less effective against Gram-negative compared to Gram positive bacteria. The result obtained in this work is consistent with the result observed by Saeb et al (2016) in which S. typhi was the resistant bacteria against the essential oil of C. limon leaf. A similar study was conducted by Hamdan et al (2013) on the antimicrobial activity of the essential oil of the peel and leaf of the Egyptian Cleopatra mandarin.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Indeed, the lemon leaf essential oil was less effective against Gram-negative compared to Gram positive bacteria. The result obtained in this work is consistent with the result observed by Saeb et al (2016) in which S. typhi was the resistant bacteria against the essential oil of C. limon leaf. A similar study was conducted by Hamdan et al (2013) on the antimicrobial activity of the essential oil of the peel and leaf of the Egyptian Cleopatra mandarin.…”
supporting
confidence: 92%
“…Although the growth of all examined microorganisms was inhibited by different concentrations of lemon leaf essential oil, the result of disc diffusion showed B. cereus and S. typhi were the most sensitive and resistant bacteria against the essential oil, respectively. Similar results were also reported by others indicating that the essential oil of citrus leaf was active against both Gram positive and Gram negative bacteria, thought it was more effective on Gram-positive strains (33,(36)(37)(38). Indeed, the lemon leaf essential oil was less effective against Gram-negative compared to Gram positive bacteria.…”
supporting
confidence: 89%
“…The antibacterial activity of the essential oils obtained from C. limon leaf was higher against Gram-pos itive bacteria such as S. aureus and B. subtilis than against gram-negative bacteria like E. coli and S. typhimurium. 10 Lawal et al conducted phytochemical analysis and evaluated the antibacterial activities of C. senensis peel extract against Salmonella paratyphi and Aeromonas hydrophila. The results of the phytochemical analysis showed the presence of flavonoids, alkaloids, saponins, tannins, triterpenoids, phytosterols and steroids and found that the bacterial isolates were sensitive to the C. senensis peel extract with MIC of 0.25-2.5 mg/mL and MBC of 0.5-5.0 mg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…6 Many Citrus species are known for their antimicrobial activity and phytochemical compounds. [7][8][9][10] In addition, Pandey et al reported antifungal activity and phytochemical compounds of the hydroalcoholic extracts of C. limon peel. Some studies have shown the presence of tannins, reducing sugar and flavonoids in the C. limon peels, whereas glycosides and saponins were absent.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that limonene and other metabolites which is belong to alkaloids, flavonoids, steroids, terpenoids, saponins, cardiac glycosides as active compound of Citrus spp could inhibit the growth of E. coli, S. aureus, Salmonella thypiimurium and Bacillus cereus cells [4,16,17]. Another study showed that the essential oils of cinnamon, oregano, thyme, and clove attribute to the existence of cinnamaldehyde, carvacrol, thymol, and eugenol, which is possess similar activities against L. monocytogenes, Salmonella typhimurium, E. coli, Brochothrix thermosphacta, and Pseudomonas fluorescens [18].…”
Section: 1antibacterial Activity Of Essensial Oilsmentioning
confidence: 99%